Anzaldua and Gomez-Pena: Two Different Expressions of Subjectivities Within the Transient Borders of Postmodernism - Fernandes, Gisele Manganelli [UNESP]; Terezinha Malvezzi, Maria Jose [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2016)
This is a discussion of The New World Border (1996), by Guillermo Gomez-Petia, and Borderlands/La Frontera: The New Mestiza (1999), by Gloria Anzaldua, whose aim is to emphasize the different Chicano subjectivities shown in the two texts. The study proposes an interaction between performance and literary language, in order to highlight the power of voices silenced in the past and now conveyors of ideas with the plurality of postmodern art. Gomez-Pena's and Anzaldua's discourses open perspectives to the production of new artistic forms written in verse and prose, in English and in Spanish. These challenging narratives reveal the rupture of not only physical borders but also that of literary genres. This work addresses the importance of the literature produced by Chicanos to American cultural life.
Keywords: Chicano Literature; Guillermo Gomez-Pena; Gloria Anzaldua; Subjectivities